Factors Influencing Purchase Intention with Brand Awareness as a Mediator on Local Fashion Brand Products - Dewi Ratnasari; Erilia Kesumahati (UNIVED Press, 2024)
This research aims to know which factors are more affective to increasing and attracting consumer purchase intentions in local fashion brands. This research used quantitative method by distributing questionnaires which obtains as many as 475 respondents with a population of people who have purchased or used local fashion products in Indonesia. The data analysis method uses PLS-SEM through SmartPLS 3.0. The results of the study show that several factors have a significant effect on purchase intention such as product quality and brand awareness. Meanwhile brand awareness mediates the relationship between purchase intention and social media marketing and addition brand awareness also mediates the relationship between purchase intention and celebrity endorser. This study show that local fashion brand business must pay more attention to product quality factors and build awareness of their business brand. Creating high brand awareness in the community will be very influential for businesses to be able to know that there business exists.